STRATEGI PENGEMBANGAN WISATA SYARIAH BERBASIS BUDAYA DI KOTA CIREBON - Anggara Disuma (UIN Siber Syekh Nurjati Cirebon, 2018)
ABSTRACTIn line with the world tourism trend that leads to the comfort of worship for Muslim tourists as an important element in the tour. The transformation of tourism development in Cirebon city is expected to be aligned and take a significant role as the center of the development of sharia tourism located in West Java. From the in-depth study using SWOT analysis (Strenght, Weaknesses, opportunities, threats) Cirebon city has the advantage of tourism, especially in the field of history, art, culture and culinary that sucked the interest of tourists visiting, therefore there are some recommendations that can be done by the parties to be used as a reference strategy in developing the existing cultural based tourism in the city of Cirebon: (1) Hopefully the realization of cooperation between parties involved in developing Islamic tourism in the city of Cirebon. (2) Increasing the capacity of managers and human resources in the vicinity of sharia tourism by holding seminars, training, guidance, comparative study, socialization and movement of conscious Islamic tourism community. (3) The management and the surrounding community must have changed the mindset that syariah tourism is built and offered based on the satisfaction and comfort of tourists, especially Muslim tourists who want comfortable travel that includes the fulfillment of the activities of worship according to Islamic Shari'a.Keywords: Development of Sharia Tourism, Art Tourism, Cultural Tourism, Historical Tourism, Culinary Tourism, Swot Analysis ABSTRAKSejalan dengan tren pariwisata dunia yang mengarah kepada kenyamanan beribadah bagi wisatawan muslim sebagai unsur penting dalam berwisata. Trasformasi perkembangan pariwisata di kota Cirebon pun diharapkan selaras dan mengambil peran signifikan sebagai pusat perkembangan wisata syariah yang berada di kawasan Jawa Barat. Dari kajian mendalam menggunakan analisis SWOT (Strenght, Weaknesses, opportunities, threats) kota Cirebon memiliki keunggulan wisata terutama dalam bidang sejarah, seni, budaya dan kuliner yang banyak menyedot animo wisatawan berkunjung, karenanya ada beberapa rekomendasi yang dapat dilakukan pihak terkait guna dijadikan acuan strategi dalam mengembangankan wisata syariah berbasis budaya yang ada di Kota Cirebon : (1) Diharapkan terwujudnya kerjasama antar pihak terkait dalam mengembangkan wisata syariah di Kota Cirebon. (2) Meningkatan kapasitas pengelola dan sumber daya manusia di sekitar daerah wisata syariah dengan mengadakan seminar, pelatihan, pembinaan, studi banding, sosialisasi dan gerakan masyarakan sadar wisata syariah. (3) Pihak pengelola dan masyarakat sekitar harus sudah merubah mindset bahwa pariwisata syariah dibangun dan ditawarkan berdasarkan kepuasan dan kenyamanan wisatawan terutama wisatawan muslim yang menginginkan kenyaman berwisata yang mencakup pemenuhan aktifitas ibadah menurut syariat Islam.Kata Kunci : Pengembangan Wisata Syariah, Wisata Seni, Wisata Budaya, Wisata Sejarah, Wisata Kuliner, Analisis Swot